Landasan Teori Metodologi Penelitian dalam Ilmu Komputer: Analisis Pendekatan Kuantitatif dan Kualitatif - Farhan Amar Pramudya; M. Alfatoni Muarrip; Sigit Muslim Anggoro Pratono; Jundi Haqqoni; Radhifan Mardhi; Mhd Furqan (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
This study discusses the theoretical foundations of research methodology in computer science by analyzing quantitative and qualitative approaches. The rapid development of computer science requires appropriate research methods to ensure the validity and reliability of findings. This study aims to examine the characteristics, advantages, limitations, and applications of quantitative and qualitative methods in computer science research. The method used is a literature review of national and international scientific publications relevant to research methodology in computer science. The results show that quantitative approaches are suitable for measurement-based, experimental, and algorithm performance studies, while qualitative approaches are more appropriate for exploratory research, user experience analysis, and system evaluation in social contexts. This study is expected to provide theoretical guidance for researchers in selecting appropriate research methodologies.